Evaluation of Different Anthropometric Indicators for Screening for Nonalcoholic Fatty Liver Disease in Elderly Individuals - Yan Zhang; Bo Li; Nan Liu; Peixi Wang; Jinghua He (International Journal of Endocrinology)
Objective. To explore the anthropometric indicators suitable for screening for nonalcoholic fatty liver disease (NAFLD) in the elderly population. Methods. This cross-sectional study screened subjects over 65 years, who had undergone a physical examination in 2019. Their height, weight, waist circumference, and fasting blood glucose and triglyceride levels were measured. Body mass index (BMI), waist circumstance (WC), waist-to-height ratio (WHtR), relative fat mass (RFM), ponderal index (PI), conicity index (CI), lipid accumulation product (LAP), and body shape index (ABSI) were calculated. Statistical analyses were performed using the Chi-square test, logistic regression, and receiver operating characteristic (ROC) curve. Subjects. Of a total of 4985 subjects, 1173 diagnosed with NAFLD and 3812 without NAFLD were included. Results. The NAFLD group had increased BMI, WC, WHtR, RFM, PI, CI, and LAP. ABSI was only significantly different in males between the groups. Logistic regression analysis showed that RFM was an effective prognostic factor for males with NAFLD, and LAP, BMI, and WC were effective prognostic factors for females. ROC curve analysis showed that LAP played a significant role in the prediction of NAFLD. Conclusion. LAP is closely related to the occurrence of NAFLD and could be an efficient screening and treatment tool for NAFLD in the elderly people. Lay Summary. We conducted a screening and study of nonalcoholic fatty liver disease in the elderly population by determining the association between obesity indexes and nonalcoholic fatty liver disease. We found that LAP is practical, easy-to-measure tool for screening and studying NAFLD in the high-risk community elderly population, making it a valuable indicator in research.